A sacro‐caudal spinal cord choroid plexus papilloma in a shar‐pei dog. (3rd June 2013) - Giannuzzi, A. Pasquale; Gernone, F.; Ricciardi, M.; De Simone, A.; Mandara, M. Teresa
<x xml:space="preserve">Abstract</x> A seven‐year‐old shar‐pei dog was referred because of severe lumbosacral pain and faecal incontinence of 20 days' duration. Neurological examination was characterised by plegic tail, absence of perineal reflex, dilated anus, perineum and tail analgesia, and severe lumbosacral pain. The neurological clinical signs were suggestive of a selective lesion involving sacral and caudal spinal cord segments and/or related nerve roots. A magnetic resonance imaging of lumbosacral spine was performed and was suggestive of an intradural lesion. Primary or secondary neoplasia was considered as the most probable differential diagnosis. The dog was euthanased upon the owner's request. Histopathological examination confirmed the presence of an intradural‐extramedullary neoplastic tissue enveloping intradural tract of spinal nerve roots. On the basis of histological and immunohistochemical findings, a diagnosis of well‐differentiated choroid plexus papilloma was made. To the authors's knowledge, this is the first case of primary or metastatic spinal choroid plexus papilloma in dogs.